Dampak K-Pop terhadap Akhlak Sesama Manusia pada Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Padang - Muhammad Irfan Maulana; Indah Muliati (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The entry of K-Pop culture has an impact on its fans. This study aims to find out in depth how the impact of K-Pop on the morals of fellow human beings on social media. Qualitative method, using purposive sampling technique / The data source is students who know the ins and outs of K-Pop, using observation, interview, documentation and document analysis data collection techniques, and will be analyzed using a qualitative approach by using data reduction, data presentation, and conclusion/verification. The positive impact of K-Pop on the morals of fellow human beings on social media for students; increasing friendship, conducting fundraising on social media, being careful in using social media. The negative impact of K-Pop on the morals of fellow human beings on social media for students; liking comments that contain hate speech on social media, making fanwars or hateful comments on social media with inappropriate words, creating anonymous accounts with names and K-Pop profile photos so that they are freer to express themselves on social media and leave no digital footprint. The positive impact of K-Pop on the morals of fellow human beings on social media for students: networking, social responsibility, caution in using social media, The negative impact of K-Pop on the morals of fellow human beings on student social media; Uploading photos and videos of K-Pop idols showing nakedness, debating on social media, and creating anonymous accounts so they are freer on social media and don't leave digital footprints when doing negative things on social media